Tokenized carbon credits in voluntary carbon markets: the case of KlimaDAO - Ballesteros-Rodríguez, Alberto; De-Lucio, Juan; Sicilia, Miguel-Ángel (Frontiers in Blockchain, 2024)
The voluntary carbon market offers a flexible and cost-effective way to reduce greenhouse gas emissions, which has led to increased interest in these markets. Within the decentralized finance ecosystem, Decentralized Autonomous Organizations leverage the tokenization of carbon credits to enhance efficiency and transparency. KlimaDAO, established in August 2021, aims to accelerate the adoption of carbon markets by integrating blockchain technology to facilitate transparent, secure, and accessible carbon trading. This study analyzes the evolution of KlimaDAO by evaluating its market capitalization, token prices, staking participation, carbon credit retirements, market participation, and concentration. The analysis reveals that while KlimaDAO initially achieved significant engagement and activity, it now faces challenges associated with market maturity and participant retention. Finally, the study highlights the importance of standardization and regulatory frameworks to enhance interoperability, transparency, and legitimacy within the tokenized carbon market.